2018
DOI: 10.7567/jjap.57.100312
|View full text |Cite
|
Sign up to set email alerts
|

Band alignment of indium–gallium–zinc oxide/β-Ga2O3 $(\bar{2}01)$ heterojunction determined by angle-resolved X-ray photoelectron spectroscopy

Abstract: The energy band offsets between indium–gallium–zinc oxide (IGZO) and β-Ga2O3 were examined by angle-resolved X-ray photoelectron spectroscopy (AR-XPS). The Ga 2p spectra from the heterojunction contributed by the upper IGZO film and the β-Ga2O3 substrate were deconvoluted into two sub-peaks with the binding energy difference of 0.3 eV, in good agreement with the theoretical model. Meanwhile, the bandgaps of IGZO and β-Ga2O3 were measured to be 3.44 ± 0.1 and 4.64 ± 0.1 eV from the ultraviolet–visible (UV–vis) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
1
1
1
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24][25][26] In addition, common semiconductor heterojunctions have been reported as well, including Si, SiC, GaN, AlN, and IZGO. [27][28][29][30][31][32] Measuring band offsets for the InN/β-Ga 2 O 3 heterojunction is thus complementary to the reported results for the other III-Nitride materials AlN and GaN. Particularly for AlN, Sun et al have reported β-Ga 2 O 3 growth on AlN substrate, whereas Chen et al have deposited AlN by plasma and thermal atomic layer deposition on β-Ga 2 O 3 .…”
supporting
confidence: 73%
“…[16][17][18][19][20][21][22][23][24][25][26] In addition, common semiconductor heterojunctions have been reported as well, including Si, SiC, GaN, AlN, and IZGO. [27][28][29][30][31][32] Measuring band offsets for the InN/β-Ga 2 O 3 heterojunction is thus complementary to the reported results for the other III-Nitride materials AlN and GaN. Particularly for AlN, Sun et al have reported β-Ga 2 O 3 growth on AlN substrate, whereas Chen et al have deposited AlN by plasma and thermal atomic layer deposition on β-Ga 2 O 3 .…”
supporting
confidence: 73%
“…[51,52,[54][55][56][57][58][59][60][61][62][63][64], the present mixed-phase Ga 2 O 3 films had a large band offset including ∆E V and ∆E C compared with previous research. The band offset of m-Ga 2 O 3 film in the present study completely meets the interface's requirements for the driving force of separating electron-hole pairs.…”
contrasting
confidence: 54%
“…Therefore, the band alignment between the semiconductors and Ga 2 O 3 should be taken into account for the design of an n-N isotype heterostructure with the type-II energy band alignment. The band alignments of Ga 2 O 3 with other wide bandgap semiconductors and dielectric layers have been investigated elsewhere [67,[340][341][342][343][344][345][346][347][348][349][350].…”
Section: Ga 2 O 3 Heterostructures-based Photodetectorsmentioning
confidence: 99%